Reproductive System Evaluation in Anestrus Buffaloes by Ultrasound and Antioxidants Profile in Basrah Governorate, Iraq (Indian Journal of Animal Production and Management, 2026)
The research study aimed to explore the reasons for buffaloes experiencing  anestrus during their breeding season in Basrah governorate, Iraq. The  research included a sample of 52 buffaloes suffering from anestrus and  another five in the estrus phase. The reproductive system of these animals  was examined to evaluate the causes of anestrus using trans-rectal  ultrasonography. Antioxidant enzymes, catalase (CAT), superoxide dismutase  (SOD), glutathione peroxidase (GSH-px), and the level of malondialdehyde  (MDA) were measured in the blood of anestrus buffaloes and compared with  those of normal cyclic buffaloes. Ultrasonographical results revealed that  the infertile buffaloes suffered from ovarian inactivity, anovulatory follicles,  persistent corpus luteum, and luteal cysts at rates of 34.16%, 21.15%, 17.30%,  and 13.46%, respectively. The research found that 13.46% of buffaloes with  normal estrous cycles experienced silent estrus. The results also showed a  significant decrease (P
Keywords: buffaloes, infertility, ultrasonography, antioxidant